Enhancement of anti-influenza A virus cytotoxicity following influenza A virus vaccination in older, chronically ill adults. - Gorse, G J (1990)
We studied anti-influenza cytotoxicity by bulk peripheral blood mononuclear leukocyte (PBL) cultures derived from older, chronically ill volunteers undergoing vaccination. Vaccinees received either cold-recombinant, live-attenuated influenza A/Korea/1/82 (H3N2) virus intranasally or inactivated monovalent influenza A/Taiwan/1/86 (H1N1) subvirion vaccine intramuscularly. PBL were collected pre- and postvaccination and in vitro stimulated by autologous PBL infected with influenza A virus homologous and heterosubtypic to the respective vaccine strain. Cytotoxicity was measured against influenza A virus-infected autologous and human leukocyte antigen (HLA)-mismatched PBL targets infected with influenza A virus homologous or heterosubtypic to the vaccine virus strain. Vaccinees infected with the live-attenuated virus developed significant rises in mean anti-influenza, HLA-restricted cytotoxicity that was cross-reactive against influenza A viruses homologous and heterosubtypic to the vaccine virus. The enhanced cross-reactive cytotoxicity was inducible postvaccination by in vitro stimulation with autologous PBL infected with the homologous influenza A (H3N2) virus and with influenza A (H1N1) virus. In contrast, after vaccination with inactivated monovalent subvirion vaccine, volunteers developed significant increases in mean anti-influenza, HLA-restricted cytotoxicity only against autologous PBL infected with homologous influenza A (H1N1) virus. Increased cytotoxicity occurred only after in vitro stimulation with autologous cells infected with homologous influenza A (H1N1) virus. Mean gamma interferon levels in supernatant fluids of influenza A virus-stimulated effector PBL did not increase postvaccination, despite increased levels of anti-influenza cytotoxicity displayed by the effector cells. We conclude that the live-attenuated influenza A virus infection induced a broader range of enhanced anti-influenza cytotoxicity than did the inactivated subvirion vaccine.